2015
DOI: 10.1057/jors.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Managing transshipments in a multi-retailer system with approximate policies

Abstract: Using the right transshipment policy is important when transshipments are exercised under demand uncertainty. Optimal transshipment policy can be quite complex in a multi-firm system as optimal actions depend on all system variables. Moreover, both how to select requested retailer and how to respond to requests are in question. We introduce simple, close-to-optimal heuristic transshipment policies for multiple retailers. We first show that heuristic policies may perform even better than self-optimal policy, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The random selection rule is commonly assumed in the literature. In fact, Comez-Dolgan and Fescioglu-Unver (2015) state that this rule performs quite well. Archibald et al (2009) suggest a different selection criterion based on the fair charge for the transshipped inventory.…”
Section: Transshipmentsmentioning
confidence: 98%
“…The random selection rule is commonly assumed in the literature. In fact, Comez-Dolgan and Fescioglu-Unver (2015) state that this rule performs quite well. Archibald et al (2009) suggest a different selection criterion based on the fair charge for the transshipped inventory.…”
Section: Transshipmentsmentioning
confidence: 98%
“…Mishra et al [19] make an effort that integrates both inventory and transshipment components in the study of multi-location inventory systems. Çömez−dolgan et al [7] introduce simple, close-to-optimal heuristic transshipment policies for multiple retailers. It is shown that heuristic policies may perform even better than self-optimal policy.…”
Section: Transshipment Policymentioning
confidence: 99%
“…Glazebrook et al [9] proposed a hybrid transshipment strategy which exploited economies of scale by moving excess inventory between traditional retail channels to prevent future stock-out in addition to meeting immediate stock-out. Çömez-Dolgan and Fescioglu-Unver [10] studied the question of whether or not a retailer should always satisfy the transshipment request from other retailers, and suggested that it was centrally optimal to satisfy all the transshipment requests when only few retailers stayed in the system. Çömez et al [11] built a flexible transshipment Yang, Zhang, Zhang, Liu: Cooperative Inventory Strategy in a Dual-Channel Supply Chain … 367 policy that allowed the retailer to reject a transshipment request on one day but accepted another transshipment request a few days later, instead of extreme transshipment strategies such as complete inventory sharing or no inventory sharing.…”
Section: Literature Reviewmentioning
confidence: 99%